The Relationship between Virtual Visits and Family Satisfaction of ICU Patients at UGM Academic Hospital - Hidayanto, Muhammad Nur; Pitajeng, Mutik Sri; Sujalmo, Purwadi; Ratnasari, Etika (Rumah Sakit Akademik Universitas Gadjah Mada, 2025)
Background: The visiting policy to the hospital changed following the pandemic situation. There was a restriction to ICU patients getting visits from their relatives or families during their admission. This policy aimed to prevent transmission and optimize care for patients. An online visit was implemented to provide a visit experience to patients and their families during ICU hospitalization. Visitation was associated with family satisfaction of ICU patients but an analysis of the relationships between virtual visits and family satisfaction in ICU has not been conducted. Identify relationships between online visit and patient’s family satisfaction with ICU.Materials and methods: An online survey of ICU patients' family members who were admitted to ICU Arjuna 5 RSA UGM in 2020-2022 was done.Results: 34 of 36 family members of ICU patients completed the online survey questionnaire. Most participants experienced online visits (85.3%) and had high levels of satisfaction with the ICU. The average score of their satisfaction with the ICU was (68.6±21,1). However, the Fisher test between online visits andthe patient’s family satisfaction with ICU resulted in a p-value of=0.56. P value >0.05 meant no significant relationship between both variables.Conclusion: there was no significant relationship between online visits and patient family satisfaction with the ICU. A high level of family satisfaction in the ICU might be influenced by other factors that are required to be studied.